2014
DOI: 10.1002/ente.201402010
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐Ion Batteries with a Wide Temperature Range Operability Enabled by Highly Conductive sp3 Boron‐Based Single Ion Polymer Electrolytes

Abstract: We report excellent operability of Li‐ion batteries equipped with selected sp3 boron‐based single‐ion polymer electrolyte membranes (SIPEs) in the temperature range of 25–100 °C. The high performance of the batteries is attributed to the high ionic conductivity of the SIPEs, superior interfacial contacts between the SIPE membranes and the electrodes, and the sizes of the mesopores in the membranes being appropriate for ion transport. It is demonstrated that the use of organic solvents in the SIPE membranes doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…[20] Unfortunately, the low lithium ion transference number ( ) < + t Li 0.3 , associated with the high mobility of the salt anion, results in the formation of strong concentration gradients during battery operation with deleterious effects on the lithium dendritic growth and limited power delivery. [22] In addition, the lithium ion transference number of SIPEs is close to unity, [23][24][25][26] whereas the value for the dual-ion (LiPF 6 ) electrolyte is as low as 0.3. Previous studies have demonstrated that SIPEs possess high thermal and water stability, wide electrochemical window, strong mechanical strength, and low cost.…”
Section: Introductionmentioning
confidence: 98%
“…[20] Unfortunately, the low lithium ion transference number ( ) < + t Li 0.3 , associated with the high mobility of the salt anion, results in the formation of strong concentration gradients during battery operation with deleterious effects on the lithium dendritic growth and limited power delivery. [22] In addition, the lithium ion transference number of SIPEs is close to unity, [23][24][25][26] whereas the value for the dual-ion (LiPF 6 ) electrolyte is as low as 0.3. Previous studies have demonstrated that SIPEs possess high thermal and water stability, wide electrochemical window, strong mechanical strength, and low cost.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4] The concept of single ion polymeric electrolyte (SIPE) was proposed with the aim to overcome most of the problems associated with the current electrolytes, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] such as severe concentration polarization and potential safety hazard. [1][2][3][4] The concept of single ion polymeric electrolyte (SIPE) was proposed with the aim to overcome most of the problems associated with the current electrolytes, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] such as severe concentration polarization and potential safety hazard.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic conductivity of the membrane was calculated to be 1.47 Â 10 À4 S cm À1 at room temperature, which is comparable to the values of most reported gel SIPEs. 35,37 The highest ionic conductivity at 80 C is 5.32 Â 10 À4 S cm À1 . As a consequence, the glass transition temperature of the polymer is raised substantially (over 300 C).…”
Section: Resultsmentioning
confidence: 98%